Phylogenetic structure and ecological and evolutionary determinants of species richness - Qian, Hong; Field, Richard; Zhang, Jin-Long; Zhang, Jian; Chen, Shengbin (Wiley, 2016)
Aim: Site-level species richness is thought to result from both local conditions and species’ evolutionary history, but the nature of the evolutionary effect, and how much it underlies the correlation with current environment, are debated. Although tropical conservatism is a widely used explanatory framework along temperature gradients, it is unclear whether cold tolerance is primarily a threshold effect (e.g. freezing tolerance) or represents a more continuous constraint. Nor is it clear whether cold tolerance is the only major axis of conservatism or whether others, such as water-stress tolerance, are additionally important or trade-off against cold tolerance. We address these questions by testing associated predictions for forest plots distributed across 35° latitude.